ANALYSIS OF ENERGY SPECTRA BY THE VORTEX METHOD WITH ARTIFICIAL TURBULENCE - Ogami, Y.; Nishiwaki, K.; Yoshihara, Y. (Revista de Engenharia Térmica, 2004)
First, in order to use as an inlet condition for turbulent simulation, a method is presented which produces numerically an artificial turbulence, namely, a series of velocity fluctuations of which frequency is Gaussian, and energy spectrum and root mean square correspond to the given ones. Besides, the fluctuation data are determined by the characteristic parameters of turbulent flows such as the inlet mean velocity, the kinematic viscosity, the Kolmogorov scale and the integral time scale. Our examples show excellent accuracy and flexibility of the method. Secondly, the vortex method has been studied to see the ability of the method to deal with turbulent flows. It is found that the energy spectra produced by this agree well with the ones given as the inlet condition, and that the vortex method is able to produce turbulent flows with the given parameters described above.